Coronary event and case fatality rates in an English population: results of the Oxford myocardial infarction incidence study. The Oxford Myocardial Infarction Incidence Study Group. - Volmink, J; Newton, J; Hicks, N; Sleight, P; Fowler, G; Neil, H (1998)
OBJECTIVES: To determine coronary event and case fatality rates in an English population aged less than 80 years in Oxfordshire, and to compare these rates with those reported by the UK monitoring trends and determinants of cardiovascular disease (MONICA) centres in Scotland and Northern Ireland and those ascertained in Oxfordshire in 1966-67. DESIGN: A population wide surveillance study conducted in 1994-95 using prospective and retrospective case ascertainment. SETTING: A resident population in Oxfordshire of 568,800. SUBJECTS: Patients with suspected myocardial infarction or coronary death. OUTCOME MEASURES: A diagnosis of definite or possible myocardial infarction or coronary death using WHO MONICA diagnostic criteria based on symptoms, electrocardiograms, cardiac enzymes, necropsy findings, and past medical history. RESULTS: The annual rate for a first or recurrent coronary event per 100,000 population aged less than 65 years in 1994-95 was 273 for men and 66 for women after age adjustment to a standard world population. Rates in the age group 65-79 years were 1350 for men and 677 for women. Between 1966-67 and 1994-95, the age standardised event rate in the age group 30-69 years decreased significantly by 33% (95% confidence interval (CI) 44 to 21) in men, and there was a non-significant reduction of 8% (95% CI -33 to 17) in women. The age standardised 28 day case fatality rates also decreased significantly by 28% (95% CI 41 to 15) in men and by 32% (95% CI 55 to 9) in women. CONCLUSIONS: The coronary event rate in Oxfordshire was much lower than rates reported by MONICA centres in Glasgow and Belfast, and similar to rates reported by MONICA centres in France and northern Italy. The substantially lower event rate accounts for lower coronary heart disease mortality in Oxfordshire than in Scotland and Northern Ireland. The reduced coronary mortality in this region is attributable to declines in coronary event and case fatality rates.